Three new Lepanthes (Orchidaceae: Pleurothallidinae) from the Alto de Ventanas ecoregion in Antioquia, Colombia - Vieira-Uribe, Sebastián (Universidad de Costa Rica, 2019)
Abstract. Three new species of the genus Lepanthes from the Alto de Ventanas ecoregion in the central Andes of Antioquia, Colombia, are described and illustrated. Lepanthes sabinadaleyana is similar to L. lycocephala but it is distinguished by the narrowly ovate leaves and the lip with oblong-obovate blades with an ovoid, obtuse appendix. Lepanthes cissyana is similar to L. ballatrix, but it differs by its purple lip with elliptical blades and a semicircular, concave body with two long, pubescent appendices in the sinus. Lepanthes dougdarlingii is similar to L. hortensis but can be distinguished by the prolific habit and the appendix of the lip lingulate to oblong, pubescent, with a concave depression in the middle, an apical glandlike structure and a tuft of hairs on the abaxial surface near the apex.